A highly conductive, transparent molecular charge-transfer salt with reversible lithiation. Issue 50 (5th June 2019) - Guan, Ying-Shi; Hu, Yong; Zhang, Hanguang; Wu, Gang; Yan, Hao; Ren, Shenqiang
Abstract : Here, we describe the high conductivity in a molecular charge-transfer hydrocarbon both as a bulk solid and films. Abstract : Here, we describe the high conductivity in a molecular charge-transfer hydrocarbon both as a bulk solid and films. In particular, the high electrical conductivity (∼30 S cm −1 ) and transparency (∼80%) of the TTF–TCNQ thin film allowed us to develop its application in all-organic freestanding photodetectors. More importantly, the fabricated TTF–TCNQ thin film can be used as a lithium-ion battery electrode with a specific capacity of ∼250 mA h g −1 .